Defining foreign language needs among pre-service CLIL teachers - Estrada Chichón, José Luis (2022)
CLIL (Content Language Integrated Learning) teacher training represents an educational challenge, where language competence and performance play a key role. So, the objective of the present research paper is to uncover the training needs of pre-service CLIL teachers (i.e., bachelor’s degree in Primary Education students, 2020-21) at the University of Cádiz (Spain) concerning their English Foreign Language (EFL) skills. This is a mixed-methods research with a descriptive approach, in which the main research tool is The CEFR ALTE Skill Level Summaries (Council of Europe, 2001). The data analysis is based on a statistical study supported by beliefs of the informants using a quiz-based assessment tool (Socrative). The results reveal that written skills prevail over oral skills in EFL terms; there still exists a low number of qualified pre-service CLIL teachers in EFL; they have not yet achieved the necessary EFL proficiency to teach CLIL subjects; and finally, methodological training is also required and not just language training as far as CLIL teaching is concerned. Final recommendations are suggested.